Optimizing Alumnus Contributions in Public Relations Management: A Study on P4NJ’s Role - Abu Yasid Albustomi; Hefniy; Abdul Wahid Zaini (Managere: Indonesian Journal of Educational Management, 2024)
This research focuses on the role of Alumnus and social media strategies in building reputation and branding. With a qualitative approach based on case studies, this study aims to explore how Alumnus contribute to the reputation of the institution and how social media, particularly Instagram and Facebook managed by P4NJ, support pesantren branding. Data was collected through in-depth interviews, observations, and documentation. Respondents consisted of Alumnus, P4NJ administrators, and people who were directly related to pesantren activities. The data were analyzed using reduction, presentation, and verification techniques to obtain structured and valid findings. The results of the study show that Alumnus have a strategic role in supporting the reputation of the pesantren through their active involvement in promotion, fundraising, and community empowerment programs. Social media has proven to be an effective tool to support pesantren branding, with engaging visual content and active interaction creating a strong emotional connection with the audience. The combination of Alumnus involvement and the use of social media has a significant impact on increasing the positive image of pesantren at the local, national, and international levels. This research enriches the literature on Islamic education by providing new insights into the synergy between tradition and technology in building religious-based educational institutions. The implication of this research is that pesantren can utilize Alumnus as a strategic asset to support their reputation and integrate digital technology to reach a wider audience. This research also opens up space for more in-depth follow-up research related to the role of social media in Islamic education.